A well-preserved ‘placoderm’ (stem-group Gnathostomata) upper jaw from the Early Devonian of Mongolia clarifies jaw evolution - Martin D. Brazeau; Haobo Yuan; Sam Giles; Anna L. Jerve; E. Zorig; Ya. Ariunchimeg; Robert S. Sansom; Robert C. Atwood (Royal Society Open Science, 2023)
The origin of jaws and teeth remains contentious in vertebrate evolution. ‘Placoderms’ (Silurian-Devonian armoured jawed fishes) are central to debates on the origins of these anatomical structures. ‘Acanthothoracids’ are generally considered the most primitive ‘placoderms’. However, they are so far known mainly from disarticulated skeletal elements that are typically incomplete. The structure of the jaws—particularly the jaw hinge—is poorly known, leaving open questions about their jaw function and comparison with other placoderms and modern gnathostomes. Here we describe a near-complete ‘acanthothoracid’ upper jaw, allowing us to reconstruct the likely orientation and angle of the bite and compare its morphology with that of other known ‘placoderm’ groups. We clarify that the bite position is located on the upper jaw cartilage rather than on the dermal cheek and thus show that there is a highly conserved bite morphology among most groups of ‘placoderms’, regardless of their overall cranial geometry. Incorporation of the dermal skeleton appears to provide a sound biomechanical basis for jaw origins. It appears that ‘acanthothoracid’ dentitions were fundamentally similar in location to that of arthrodire ‘placoderms’, rather than resembling bony fishes. Irrespective of current phylogenetic uncertainty, the new data here resolve the likely general condition for ‘placoderms’ as a whole, and as such, ancestral morphology of known jawed vertebrates.